2022
DOI: 10.3390/diagnostics12112600
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Urinary Extracellular Vesicles and Immune Mediators as Biomarkers of Kidney Injury in COVID-19 Hospitalized Patients

Abstract: Kidney injury is an important outcome associated with COVID-19 severity. In this regard, alterations in urinary extracellular vesicles (uEVs) could be detected in the early phases of renal injury and may be reflective of the inflammatory process. This is an observational study performed with a case series of COVID-19 hospitalized patients presenting mild-to-critical disease. Total and podocyte-derived uEVs were identified by nanoscale flow cytometry, and urinary immune mediators were assessed by a multiplex as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
1
0
Order By: Relevance
“…Tubules filled with vesicles are not common in the kidney samples and were detected only incidentally in the current EM study. Others have reported slightly increased levels of urinary extracellular vesicles in COVID-19 patients ( 49 ). Still, the vesicle-filled lumens of renal endothelium is of interest.…”
Section: Discussionmentioning
confidence: 96%
“…Tubules filled with vesicles are not common in the kidney samples and were detected only incidentally in the current EM study. Others have reported slightly increased levels of urinary extracellular vesicles in COVID-19 patients ( 49 ). Still, the vesicle-filled lumens of renal endothelium is of interest.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, a proteomic-based study demonstrated that changes in urinary cytokines are indeed associated with AKI development [99]. Thus, urinary proinflammatory cytokines such as TNFα, IL-1α, IL-1β, IL-16, and IL-17A and total uEVs in COVID-19 patients may identify patients that are prone to renal dysfunction [63]. Interestingly, many of these cytokines, such as MCP-1, IL-1β, and TNF-α, do overlap with the inflammatory mediators, which are upregulated by lipopolysaccharide (LPS)-induced AKI, demonstrating parallels between SARS-CoV-2-induced AKI and sepsis-induced AKI [99,100].…”
Section: Stage Descriptionmentioning
confidence: 99%
“…The isolation of urinary extracellular vesicles (uEVs) followed by the use of liquid chromatography-tandem mass spectrometry for proteomic analysis revealed nearly 300 proteins within the uEVs, including multiple protein products associated with renal and systemic diseases [62]. Another crucial study has revealed the clinical differences in uEVs and cytokines, further emphasizing the fact that EVs can be used to determine disease severity [63]. Particularly, in this study the urine samples were collected from patients with COVID-19 disease during the first days of hospitalization.…”
Section: Extracellular Vesicles As An Indicator Of Kidney Disease And...mentioning
confidence: 99%